Учетное отражение внутригрупповых операций и его влияние на консолидацию финансовой отчетности - Рудейчук, С.В. (Культура народов Причерноморья, 2013)
У статті досліджено методику облікового відображення внутрішньогрупових операцій
консолідованих груп, виявлення та розкриття особливостей елімінування (виключення), впливу
внутрішньогрупових операцій на показники консолідованої фінансової звітності.
Практична значущість полягає в розробці рекомендацій з удосконалення методичних аспектів
бухгалтерського обліку внутрішньогрупових операцій консолідованих груп у сучасних умовах
господарювання та урахування впливу елімінування (виключення) внутрішньогрупових операцій на
показники консолідованої фінансової звітності. В статье исследовано методику учетного отражения внутригрупповых операций
консолидированных групп, выявление и раскрытие особенностей элиминирования (исключения), влияния
внутригрупповых операций на показатели консолидированной финансовой отчетности .
Научная новизна заключается в обосновании теоретических положений и учетном отражении
внутригрупповых операций консолидированных групп в условиях исключения влияния внутригрупповых
операций на показатели консолидированной финансовой отчетности для эффективного управления
ресурсами группы предприятий, обеспечения их конкурентоспособностю и непрерывного осуществления
ими хозяйственной деятельности. The article addresses the accounting methods of representing intra-group transactions between
consolidated groups and eliminating the effects of intra-group transactions on financial statements.
Research methodology. Intra-group transactions result in intra-group balances as well as unrealized profit and
loss. Intra-group balances, transactions, profits and losses determined by assets such as supplies or capital must
be entirely eliminated. In preparing consolidated financial statements, the parent enterprise determines the
minority interest in the capital and the financial results of its subsidiaries. The minority interest in the enterprise
capital consists of the minority interest on the date of purchase of the subsidiary and the minority interest in the
amount of the subsidiary’s capital shift after purchase. Intra-group transaction data can be obtained from
analytical accounting reports, special profit and loss accounts and subaccounts which keep records of intragroup
transactions.
The scientific novelty of the paper results from developing the theoretical assumptions and representing intragroup
transactions in consolidated groups under conditions of eliminating the influence of intra-group
transactions on financial statements in order to ensure effective enterprise resource management,
competitiveness, and continuous activity.